Implementasi data mining untuk menganalisa pola penjualan produk cap-lang menggunakan metode associatin rule - ulfa Dwi Yanti; Ahmad Zakir; Dedy Irwan (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Data mining is operation of resourcing and using data to find patterns or relationships from large data sets. Data mining has been implemented in various aspects, one of which is in the field of product sales. The company can find out the buyer's interest by utilizing data mining to process data on sales of wind oil products. This study analyzes the search for information from wind oil sales transaction data using data mining with a priori algorithm. The results obtained are quite accurate as an analysis in conducting stock in sales transactions and with easy work steps. Making this method appropriate for the system in this study. And it is hoped that in the future they can develop this research related to the method used or the web that has been built to complement the shortcomings of this researc